Study of the spin and parity of the Higgs boson in diboson decays with the ATLAS detector - ATLAS collaboration (2842 authors); Aguilar-Saavedra, Juan Antonio; Amor Dos Santos, Susana Patricia; Anjos, Nuno; Araque, Juan Pedro; Cantrill, Robert; Carvalho, João; Castro, Nuno Filipe; Conde Muiño, Patricia; Da Cunha Sargedas De Sousa, Mario Jose; Fiolhais, Miguel; Galhardo, Bruno; et al. (My University, 2015)
Studies of the spin, parity and tensor couplings of the Higgs boson in the $H \rightarrow ZZ^{*} \rightarrow 4 \ell $ , $H \rightarrow WW^{*} \rightarrow e \nu \mu \nu $ and $H \rightarrow \gamma \gamma $ decay processes at the LHC are presented. The investigations are based on $25\,\mathrm{fb}^{-1}$ of pp collision data collected by the ATLAS experiment at $\sqrt{s}=7$  TeV and $\sqrt{s}=8$  TeV. The Standard Model (SM) Higgs boson hypothesis, corresponding to the quantum numbers $J^{P}=0^{+}$ , is tested against several alternative spin scenarios, including non-SM spin-0 and spin-2 models with universal and non-universal couplings to fermions and vector bosons. All tested alternative models are excluded in favour of the SM Higgs boson hypothesis at more than 99.9 % confidence level. Using the $H \rightarrow ZZ^{*} \rightarrow 4 \ell $ and $H \rightarrow WW^{*} \rightarrow e \nu \mu \nu $ decays, the tensor structure of the interaction between the spin-0 boson and the SM vector bosons is also investigated. The observed distributions of variables sensitive to the non-SM tensor couplings are compatible with the SM predictions and constraints on the non-SM couplings are derived.